The Destiny of Hope: The “Damned Mob” of Women Activist Writers and the Indian Removal - Carroll Clayton Savant ([sic])
“America is now wholly given over to a d – d mob of scribbling women, and I should have no chance of success while the public taste is occupied by their trash…” (Hawthorne 304). However Nathaniel Hawthorne chose to voice his frustration with the American female writer, she did play a significant social role in nineteenth-century American cultural history. Formally removed from the political discourse of their generation, women activists turned to other means for disseminating opinions and disapproval. The rising genre of the novel was one of the most effective and visible forms available to American women. Viewed as an historical artifact, the novel was steeped in social convention and cultural ideology. Therefore, when women turned to it to voice opposition to Andrew Jackson’s Indian Removal Act, they did so by embracing the traditionally-accepted methodology of the novel, but altering it through subversive language and plots to suit their critical needs. The goal of this paper is to look at the social implications that surrounded Catharine Maria Sedgwick’s Hope Leslie or Early Times in the Massachusetts and Lydia Maria Child’s Hobomok, A Tale of Early Times by an American. By setting both of these works amidst the cultural atmosphere that gave rise to Jackson’s Indian Removal, I plan to look at the social and historic impact of Child and Sedgwick’s works as these two authors wrote out in opposition to the treatment and representation of the American Indian. Within the process, I intend to note several of the significant arguments regarding women’s role in social and political policy and the ability of women writers to reach the general public through their reading audiences.